Teaching Planning and Field Experience Practice in Preparing Professional Teachers - Delvia, Melda; Sepriyanti, Nana; Kustati, Martin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
Micro teaching and field experience practice are two fundamental things in the world of Private Islamic Religious Higher Education which has an education study program. The purpose of this study was to determine the planning of micro teaching and field experience practices in preparing professional teachers at Private Islamic Universities in Padang City. The type of research used is qualitative research with a descriptive qualitative approach. The data sources in this article consist of micro teaching lecturers, field experience practice committee, dean / chairman, head of the Islamic Education department, and lecturers who have been field supervisors at Private Islamic Religious Universities at Private Islamic Religious Universities in Padang City. In collecting data, researchers used observation, interview and documentation techniques. The results showed that Private Islamic Religious Colleges have made micro teaching planning which is assigned responsibility to micro teaching lecturers, the planning stages include formulating lecture objectives, designing learning experiences that students will receive, planning lecture materials, paying attention to the availability of supporting infrastructure, and planning the final assessment process, but still not done in accordance with the theoretical references. While the planning of field experience practice, the planning carried out by the field experience practice committee has been carried out in accordance with the theoretical reference.